2017
DOI: 10.1186/s13104-017-2545-5
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of Schisto and Ladders™, an innovative health educational game for control of schistosomiasis in schoolchildren

Abstract: BackgroundSchistosomiasis remains a public health problem in many regions of the world, including Nigeria. Current control strategy involves mass drug administration with praziquantel to the endemic population. To complement and sustain on-going preventive chemotherapy, we developed a health educational game named Schisto and Ladders™ and tested its potential for the control of schistosomiasis among schoolchildren living in Imala-Odo, a highly endemic community near Abeokuta, Nigeria.MethodsOne hundred school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 20 publications
1
31
0
1
Order By: Relevance
“…Through the implementation of schistosomiasis health education session, the cognition level of schistosomiasis among primary and secondary school students was significantly improved, and the effect on primary and secondary school students was quite. This suggested that This interactive mode health education has a positive effect on the improvement of students' schistosomiasis cognitive level, the same results were obtained in some similar researches conducted in Brazil and Nigeria [30,31]. On the contrary, some non-interactive health education modes are not effective [20].…”
Section: Discussionsupporting
confidence: 60%
“…Through the implementation of schistosomiasis health education session, the cognition level of schistosomiasis among primary and secondary school students was significantly improved, and the effect on primary and secondary school students was quite. This suggested that This interactive mode health education has a positive effect on the improvement of students' schistosomiasis cognitive level, the same results were obtained in some similar researches conducted in Brazil and Nigeria [30,31]. On the contrary, some non-interactive health education modes are not effective [20].…”
Section: Discussionsupporting
confidence: 60%
“…For instance, Bieri and colleagues [13] in China used a video-based health education package to prevent new STH infections after treatment. Similarly, Ejike and colleagues [24] in Nigeria has used the health education game called Schisto and Laddders to significantly improve the knowledge, attitudes and practices of school children for the prevention and control of schistosomiasis. Health education thus plays a significant role in helminths disease prevention, by decreasing exposure risk through behavioral change, and in increasing health-seeking behavior.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…In order to have an ample sampling frame, six schools were randomly selected, at first using balloting from each cluster. Afterwards, three schools were selected randomly out of the six schools in each clusters using the second round of balloting to minimize the cofounding effect that may arise due to cross-communication among schools that shares boundary or are near each other [24]. The final randomization of participating schools to intervention was carried out by one of the researchers (blinded) who did not partake in the schools' selection procedures.…”
Section: Study Design and Selection Of Schoolsmentioning
confidence: 99%
“…21 Pengendalian schistosomiasis secara integrasi dengan menggabungkan pengobatan dan pengendalian fokus keong adalah merupakan strategi terbaik untuk menghilangkan schistosomiasis. 22 Hasil lain menunjukkan bahwa edukasi schistosomiasis di kalangan anak sekolah dapat meningkatkan pengetahuan, sikap, dan perilaku berisiko terhadap pengendalian schistosomiasis di kalangan anak-anak di daerah endemis, 23 untuk dapat memprediksi kasus schistosomiasis, efek dan berbagai tindakan pengendalian ke depan diperlukan suatu model matematis transmisi Schistosoma. 24 Habitat keong Oncomelania juga dipengaruhi oleh kondisi suhu, tipe tanah, tipe vegetasi, dan juga kecukupan air yang mendukung perkembangan keong dan juga pergerakan serkaria.…”
Section: Pembahasanunclassified